Military sports medicine clinics should continue to organise MRI prior to listing for "fast track" meniscectomy. Issue 15 (10th November 2011) - Howes, J; Wood, A M; Bell, D J; Wrigley, S; Angus, C
Abstract : Patients referred from military sports injury clinics for "Fast Track" meniscectomy are not necessarily seen prior to the day of surgery by an orthopaedic surgeon. To prevent unnecessary surgery an MRI confirms meniscal tear. We investigated whether suspected meniscal pathology requires MRI scan prior to referral, for meniscectomy or if history and examination can diagnose meniscal pathology. 47 patients attending the regional sports injury clinic with knee pain requiring an MRI scan were prospectively recorded with original diagnosis, signs, history and MRI results. Of the 47 patients 21 (45%) had meniscal tears detected on MRI. Of the 26 without a meniscal injury 8 (30%) had degenerative knees, 6 (23%) had no abnormality detected. Of the 21 patients with meniscal tears, clinical diagnosis had a specificity of 1 and sensitivity of 54% with a significant p-value of 6×10 −5 . Trauma was 90% sensitive and 64% specific with a significant p-value of 3×10 −4 . McMurray's sign was 90% sensitive and 31% specific, with a clinically insignificant p-value of 0.08. Joint line tenderness was 85% sensitive and 31% specific with an insignificant p-value of 0.92. Reduced squat was 86% sensitive and 27% specific. Using a combination of all four tests increases specificity to 85% but decreases the sensitivity to 67%, with a 3×10 −4 significant p-value. Only 2/12 patients whose overall clinical diagnosis was wrong for meniscal tears had an MRI diagnosis which would require arthroscopy. Our results demonstrate that patients referred from a military sports injury clinic still require MRI prior to surgery. While we accurately diagnosed all the meniscal tears in clinic, our specificity of 54% would have resulted in 10 (21%) patients undergoing needless arthroscopy.